DAMPAK PEMILU PRESIDEN DAN WAKIL PRESIDEN TERHADAP ABNORMAL RETURN INVESTOR - Suwaryo Suwaryo (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2008)
Research on abnormal return for investors was carried out through taking population of stock from 45 companies (emitents) that belong to LQ-45 group during period of August 2004 till February 2005. The stocks that belong to LQ-45 group are stocks that have high liquidity as well as their high capitalization value.This research was focused on an event, it was president and vice presiden election, whether it had a significant effect on investors abnormal return in capital market. The research on something that is always called Event Study has the purpose to find out whether the event has an effect on stock price an it will finally effect has an effect on stock price an it will finally effect investor’s income.To find out whether there was not a significant difference between the average abnormal return 10 days before and 10 days after the election, it was tested using two side t-test with the result that there wasn’t a significant difference. President and Vice President election event is an event that can be anticipated as its execution has been known before, so what will possibly happen is who will be chosen, and how this will have research is that the event is known before so it can be anticipated by the investors.